Evaluating Violants of Thrifting Policies on Online Platforms: A Public Sentiment Analysis Thorough Instagram - Ami Afriyani; Muhammad Taufiq Hatta Wibowo (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
The phenomenon of